To pool or not to pool? Screening of Chlamydia trachomatis and Neisseria gonorrhoeae in female sex workers: pooled versus single-site testing. (13th May 2020) - Verougstraete, Nick; Verbeke, Vanessa; De Cannière, Anne-Sophie; Simons, Caroline; Padalko, Elizaveta; Coorevits, Liselotte
Abstract : Objectives: As Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) are the most commonly reported STIs in Belgium and the majority of women infected are asymptomatic, targeted screening of patients in specified risk groups is indicated. To prevent long-term complications and interrupt transmission, extragenital samples should be included. As this comes with a substantial extra cost, analysis of a pooled sample from vaginal and extragenital sites could be a solution. In this study, we evaluated the feasibility of molecular testing for CT and NG in pooled versus single-site samples in a large cohort of female sex workers. Methods: Women were sampled from three anatomical sites: a pharyngeal, a vaginal and a rectal swab. Each sample was vortexed, and 400 µL of transport medium from each sample site was pooled into an empty tube. NAAT was performed using the Abbott RealTime CT/NG assay on the m2000sp/rt system. Results: We included 489 patients: 5.1% were positive for CT; 2.0% were positive for NG and 1.4% were coinfected, resulting in an overall prevalence of 6.5% (95% CI 4.5% to 9.1%) for CT and 3.5% (95% CI 2.0% to 5.5%) for NG. From the 42 patients positive on at least one non-pooled sample, only 5 gave a negative result on the pooled sample, resulting in a sensitivity of 94% (95% CI 79% to 99%) for CT and 82% (95% CI 57% to 96%) for NG. The missed pooled samples were all derived from single-site infections with low bacterial loads. The possibility of inadequate self-sampling as a cause of false negativity was excluded, as 4/5 were collected by the physician. Testing only vaginal samples would have led to missing 40% of CT infections and 60% of NG infections. Conclusions: Pooling of samples is a cost-saving strategy for the detection of CT and NG in women, with minimal decrease in sensitivity. By reducing costs, more patients and more extragenital samples can be tested, resulting in higher detection rates.